Hubungan antara Dukungan Sosial dengan Tingkat Stres pada Lansia di Rumah Pelayanan Sosial - Bella Aldanisa Afanda; Iskim Luthfa (Journal of Health, Medical, and Psychological Studies, 2025)
Aging is a phase of life that is closely associated with physical, psychological, and social changes, which may increase vulnerability to stress among older adults. This study aimed to examine the relationship between social support and stress levels among elderly individuals living in social care institutions. A quantitative descriptive-analytic design with a cross-sectional approach was applied. The population consisted of 204 elderly residents, with 132 respondents selected using purposive sampling. Social support was measured using a questionnaire based on House’s theory, while stress levels were assessed using the DASS-Stress instrument. Data were analyzed using Somers’ d test. The results showed that most respondents had moderate social support and experienced severe stress. Statistical analysis revealed a significant relationship between social support and stress levels (p = 0.008), although the strength of the correlation was weak. These findings indicate that social support is related to stress among the elderly, but it is not the sole determinant influencing psychological conditions. Other factors such as physical health, chronic illness, and individual coping capacity may play a more dominant role. Therefore, comprehensive and integrated interventions are needed to improve the psychological well-being and quality of life of elderly individuals in social care institutions..